The use of Red Cabbage’s anthocyanine extract as a photosensitizer on a Dye-Sensitized Nanocrystalline TiO2 Solar Cell - Maddu, Akhiruddin; Zuhri, Mahfuddin; Irmansyah, Irmansyah (Makara Journal of Technology, 2007)
The use of Red Cabbage’s anthocyanine extract as a photosensitizer on a Dye-Sensitized Nanocrystalline TiO2 Solar Cell. A solid-state dye-sensitized nanocrystalline TiO2 solar cell utilizing anthocyanin extract form red cabbage as photosensitizer was fabricated. The solar cell was formed in sandwich structure, which two electrodes sandwiching polymer electrolyte containing a redox couple (I-/I3 -). One of the electrodes, namely working electrode, TiO2 layer on TCO (transparent conducting oxide) coated glass substrate was sensitized with anthocyanin dye as electron donor in the system. Another electrode was a carbon sheet as a counter electrode. Gel electrolyte based on PEG (polyethylene glycol) containing a redox couple (I-/I3 -) used instead of liquid electrolyte in this photoelectrochemical cell. Two fabricated cells have an active area of 1 cm2 were soaked with anthocyanine dye for 1 hr and 24 hrs, respectively. The cells were tested by irradiation with halogen lamp of 24 Watt with intensity 4 mW/cm2 at a distance 30 cm. The testing results of the cells show an ideal I-V characteristic with output parameters: open circuit voltage (VOC) of 500 mV, short circuit current (ISC) of 5,6 μA and 7,2 μA for each cells, fill factor (FF) of 48% for both cells, energy conversion (η) of 0.023 % and 0,055 % for the cells with 1 hr and 24 hrs dye soaked, respectively.